Periapical cysts in dogs: 10 cases (2000–2020) - Vogel-Waski, Rebecca J.; Castejon-Gonzalez, Ana C.; Church, Molly E.; Reiter, Alexander M. (Frontiers in Veterinary Science, 2024)
ObjectiveTo characterize the clinical, diagnostic imaging, and histologic features with description of treatment outcome of periapical cysts in dogs.AnimalsTen client-owned dogs diagnosed with periapical cysts biopsied between July 1, 2000 and June 30, 2020.ProceduresMedical records of the Matthew J. Ryan Veterinary Hospital of the University of Pennsylvania were retrospectively searched to identify dogs that had surgical biopsy specimens of cavitary lesions diagnosed as odontogenic cysts and that met additional inclusion criteria. Complete medical records were reviewed.ResultsRange age and body weight of affected dogs were 2.5–12.1 years and 4.3–38.4 kg (9.5–84.7 lb), respectively. All periapical cysts were affecting the incisive bone and/or the maxilla. Nine dogs presented with a fluctuant swelling of the oral mucosa and gingiva; one dog without clinical swelling presented with a history of difficulty breathing. All cysts originated from a non-vital tooth with a structural defect (wear or fracture without pulp exposure) and/or intrinsic staining. Extraction of the associated non-vital teeth, enucleation of the cysts, and curettage of the surgical sites resulted in resolution of the clinical signs.Conclusions and clinical relevanceThe findings indicate that periapical cysts are associated with a non-vital tooth without pulp exposure. Complete evaluation of the clinical, diagnostic imaging, and histologic features of the lesion in affected dogs is necessary to differentiate periapical cysts from other odontogenic cysts and tumors.